What Could Reduce the Cost of Sugar? The Case of State-owned Sugar Mills in Bangladesh (Social Science Review, 2023)
Since the early 2000’s trade liberalization, the state-owned sugar mills in Bangladesh have started to lose competitiveness. Before that this industry used to be considered a strategic sector because sugar is an essential food and the industry creates thousands of rural employments. In 2020, the government suspended operation of six out of fifteen mills with the excuse of loss. The closure of six mills has reduced the sugar production and negatively impacted the lives of farmers, workers, and businessmen. The government is considering foreign investment without considering the potential of government investment to revive the industry. Therefore, it is important to re-examine the factors that increased the cost and find out how the state could revive the industry under its ownership. This paper analysed the data of 15 state-owned sugar mills for 14 years (2006-07 to 2019-2020) using mixed method (fixed effect regression and interview) to explain the mechanisms of the cost increase. It found that the recovery rate, price of sugarcane, availability of sugarcane, age of mills, and interest payment are the most important determinants of cost. Modernizing the mills, making sugarcane available through sugarcane price incentives, timely payment to farmers, and diversifying products could contribute to cost reduction.Social Science Review, Vol. 39(3), Dec 2022 Page 133-151